Challenges and strategies of rural community towards sustainable development - Afza Razan Salleh,; Nur Kamaliah Mustaffa,; Che Maznah Mat Isa,; Azizul Salfaizal Aziz, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Disparities between rural and urban areas continue to face the dilemma of spatial inequality in social and economic development. Sustainable development plays a major role in rural areas since it can improve their quality of life through socio-economic development whilst preserving the environment. This study is conducted to explore the knowledge and attitudes of rural communities towards sustainable development and to determine the challenges and strategies of rural communities on sustainable development. A mixed-method research approach was adopted from 131 respondents from the rural communities supported by interviews with three (3) experts in environmental and sustainability in Malaysia. The data was analyzed by using Statistical Package for the Social Sciences (SPSS) and content analysis. The respondents perceived themselves as having a good level of knowledge and attitudes towards sustainable development, however the experts opined the opposite views. Lack of infrastructure becomes the main challenges for the rural communities in achieving sustainable development and by improving basic utilities and communication services can help the rural communities to have a better lifestyle and sustainable life which are echoed by the experts. This study is significant to improve lifestyle of the rural communities and contribute to the sustainable development of the country.